Descent of fetal head during active pushing: secondary analysis of prospective cohort study investigating ultrasound examination before operative vaginal delivery. (4th October 2019) - Kahrs, B. H.; Usman, S.; Ghi, T.; Youssef, A.; Torkildsen, E. A.; Lindtjørn, E.; Østborg, T. B.; Benediktsdottir, S.; Brooks, L.; Harmsen, L.; Salvesen, K. Å.; Lees, C. C.; et al.
ABSTRACT: Objectives: To investigate if descent of the fetal head during active pushing is associated with duration of operative vaginal delivery, mode of delivery and neonatal outcome in nulliparous women with prolonged second stage of labor. Methods: This was a prospective cohort study of nulliparous women with prolonged second stage of labor, conducted between November 2013 and July 2016 in five European countries. Fetal head descent was measured using transperineal ultrasound. Head–perineum distance (HPD) was measured between contractions and on maximum contraction during active pushing, and the difference between these values (ΔHPD) was calculated. The main outcome was duration of operative vaginal delivery, estimated using survival analysis to calculate hazard ratios (HRs) for vaginal delivery, with values > 1 indicating a shorter duration. HR was adjusted for prepregnancy body mass index, maternal age, induction of labor, augmentation with oxytocin and use of epidural analgesia. Pregnancies were grouped according to ΔHPD quartile, and delivery mode and neonatal outcome were compared between groups. Results: The study population comprised 204 women. Duration of vacuum extraction was shorter with increasing ΔHPD. Estimated mean duration was 10.0, 9.0, 8.8 and 7.5 min in pregnancies with ΔHPD in the first to fourth quartiles, respectively, and the adjusted HR for vaginal delivery, using increasing ΔHPD as a continuous variable, was 1.04 (95% CI, 1.01–1.08). Mean ΔHPD was 7 mm (range, −10 to 37 mm). ΔHPD was either negative or ≤ 2 mm in the lowest quartile. In this group, 7/50 (14%) pregnancies were delivered by Cesarean section, compared with 8/154 (5%) of those with ΔHPD > 2 mm ( P  < 0.05). There was no significant association between umbilical artery pH < 7.10 or 5‐min Apgar score < 7 and ΔHPD quartile. Conclusion: Minimal or no fetal head descent during active pushing was associated with longer duration of operative vaginal delivery and higher frequency of Cesarean section in nulliparous women with prolonged second stage of labor. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.